New ornithomimosaurian (Dinosauria: Theropoda) pelvis from the Upper Cretaceous Erlian Formation of Nei Mongol, North China. (September 2022) - Yao, Xi; Sullivan, Corwin; Tan, Qingwei; Xu, Xing
Abstract: A newly identified ornithomimosaurian pelvis and sacrum from the Upper Cretaceous Erlian Formation of Nei Mongol, China is described in detail in this paper. This specimen is distinguished from previously described taxa by the presence of a combination of features that is unique among Ornithomimosauria: sacrum comprising five vertebrae with neural spines fused into a continuous plate, iliac posterior end rectangular, pubic shaft distally straight, ischial boot not broadened transversely, and ischial shaft proximally straight, distally curved, and 80 percent as long as the pubis. This specimen differs from at least some material assigned to the sympatric Archaeornithomimus asiaticus, showing that two distinct ornithomimosaurian taxa are present in this Upper Cretaceous fossiliferous rock unit. A phylogenetic analysis places LH-02-01 in a relatively early-diverging position within Ornithomimosauria, outside the two major clades Deinocheiridae and Ornithomimidae, but its relationships with other early-diverging ornithomimosaurs remain unresolved. The primitive nature of LH-02-01 adds to the evidence from fossil vertebrates that the Erlian Formation correlates with the Turonian Bissekty Formation of Uzebekistan, while the biostratigraphic evidence from non-vertebrates instead indicates a Campanian to Maastrichtian assignment for the Erlian Formation. This apparent contradiction remains unresolved, pending future research aimed at reconciling the seemingly incompatible lines of evidence.